(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
The present work describes the identification of unknown lachrymatic chemical, which were spilled during transportation caused suffocation and left several persons with tears and results panic in public. By applying chemical colour tests and gas chromatographic analysis, the chemical identified as formalin, which is used as preservative for biological specimens.